Study of the surface properties and particle-particle interactions in oleic acid-coated Fe3O4 nanoparticles - Urian Y.A. (2021)
Magnetite (Fe3O4) nanoparticles coated with organic material are of considerable importance in various areas of engineering, as well as in biomedicine. Several papers show drastic changes in the magnetic properties related to the surface effects and the particle-particle interactions strength. However, there is no consensus about the origin or mechanisms that produce these changes, which could be different depending on the particle size and shape, coating efficiency and particle-particle interaction strength. Aiming to shed light on these issues, oleic acid (OA) coated Fe3O4 nanoparticles with different sizes were synthesized by a thermal decomposition method. Structural and microscopic results revealed Fe3O4 nanoparticles with good crystallinity and almost-spherical or polyhedral shapes depending on the solvent used for the synthesis. Infrared (FTIR) spectroscopy indicated OA molecules attached to the surface of Fe3O4 NPs via bidentate (chelating and/or bridging) bonds; meanwhile, thermogravimetric analysis confirmed the presence of weakly and strongly bonded OA molecules, suggesting a successful coating of Fe3O4 NPs. Magnetization (M) vs. magnetic field (H) curves are consistent with a core/shell structure formed by magnetite/defective magnetite (maghemite) phases, in consistency with FTIR spectroscopy. It was determined lower saturation magnetization values than that expected for bulk magnetite, which was assigned to the likely presence of a fraction of iron ions in low-spin (LS) states in the defective magnetite (maghemite) layer at the particles surface. The magnetic results evidence that depending on the amount of OA coating, it is possible to tune the particle-particle separation distance, avoid particles agglomeration and particle-particle interactions. The temperature dependence of magnetization reveals the presence of non-interacting and interacting NPs. Meanwhile, AC magnetic susceptibility measurements are consistent with those results and provide features related to superparamagnetic (SPM) behavior, assigned to the non-interacting NPs, and interacting SPM behavior, assigned to the interacting NPs, whose interaction strength is not enough to lead to a spin-glass like behavior. © 2021 Elsevier B.V.